CALCUL TECHNOLOGIQUE, CINÉTIQUE ET MODÉLISATION D’UN PROCÉDÉ D’ÉPURATION DE GAZ NATUREL - BOULAKOUD Manel (My University, 2011)
A part of the Algerian natural gas is destinated to the exportation, where it should be liquefied is a necessity; this last operation is possible except if we eliminate the CO2 which the natural gas contains. The reduction of the CO2 is specifically done by different alkanolamines such as Monoethanolamine (MEA), Diethanolamine (DEA), Triethanolamine (TEA) and Methyldiethanolamine (MDEA). Our objective is to find a solvent which is adequate to the absorption and that is efficient from the technical and economic point of view. An experimental study (technical, kinetic and modeling) will be necessary to make a convenient choice for the solvent.
Keywords: absorption, MEA, carbon dioxide, gas, kinetic.